2001
DOI: 10.1182/blood.v98.1.174
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin induces apoptosis in monocyte- and CD34-derived dendritic cells but not in monocytes and macrophages

Abstract: Rapamycin (Rapa), a recently introduced immunosuppressive drug, seems to be effective in preventing acute allograft rejection. Although its antiproliferative effect on T lymphocytes has been investigated extensively, its effect on the initiators of the immune response, the dendritic cells (DCs), is not known. Therefore, the effect of Rapa on monocyte-(mo-DCs) and CD34 ؉ -derived DCs in vitro but also on other myeloid cell types, including monocytes and macrophages, was examined. The present study shows that Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
5
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(133 citation statements)
references
References 61 publications
11
116
5
1
Order By: Relevance
“…Inhibition of PI3K, ERK, or p38 in monocytes slightly induced apoptosis ( Figure 2A). As shown previously, 15 monocytes were completely insensitive for the proapoptotic activity of Rapa, demonstrating that the longevity of DCs and their precursors, ie, the monocytes, are regulated by different survival mechanisms.…”
Section: Monocytes and Dcs Differ In Their Survival Mechanismssupporting
confidence: 74%
See 2 more Smart Citations
“…Inhibition of PI3K, ERK, or p38 in monocytes slightly induced apoptosis ( Figure 2A). As shown previously, 15 monocytes were completely insensitive for the proapoptotic activity of Rapa, demonstrating that the longevity of DCs and their precursors, ie, the monocytes, are regulated by different survival mechanisms.…”
Section: Monocytes and Dcs Differ In Their Survival Mechanismssupporting
confidence: 74%
“…Like treatment of DCs with Rapa to inhibit mTOR, 15 blockade of PI3K in DCs by addition of LY294002 time-and dose-dependently induced apoptosis that was characterized by nuclear condensation and fragmentation ( Figure 2B) and DNA fragmentation (data not shown). In addition to the data obtained from GM-CSF deprivation experiments, both LY294002 and Rapa demonstrated loss of ⌬⌿ m associated with the percentage of apoptosis induced ( Figure 2C).…”
Section: Survival Requires Gm-csf Signaling Via Pi3k and Mtormentioning
confidence: 95%
See 1 more Smart Citation
“…21 Having established that rapamycin inhibited DC endocytosis, we analyzed whether this effect was due to increased apoptotic cell death. In contrast to a recent report, 22 the incidence of apoptosis at day 7 of culture was consistently low (Ͻ 10%) and was not affected significantly by rapamycin, even at a suprapharmacological dose of 100 ng/mL, as determined independently by annexin-V/7-AAD and TUNEL staining ( Figure 2D, E). Similar results were obtained with GM-CSFϩIL-4-expanded DCs and at day 4 of culture (data not shown).…”
Section: Resultscontrasting
confidence: 51%
“…We reported recently that Rapa impairs Ag uptake of murine dendritic cells (DC) (8), a finding that was subsequently confirmed in human DC (9). Moreover, it was suggested that Rapa promotes in vitro apoptosis of human DC by interfering with GM-CSF signaling (10) and suppresses in vivo DC development and function (11). DC are professional APC with a unique ability to induce and control adaptive and innate immune responses (12)(13)(14)(15).…”
mentioning
confidence: 99%